Electrical resistivity measurements of mechanically stabilized earth retaining wall backfill - Snapp, Michael Andrew (Kansas State University, 2015)
In Kansas, mechanically stabilized earth (MSE) retaining walls are typically backfilled with coarse aggregate. Current backfill material testing procedures used by the Kansas Department of Transportation (KDOT) utilize on-site observations for construction quality assurance and the American Association of State Highway and Transportation Officials standard T 288-12 (“Standard Method of Test for Determining Minimum Laboratory Soil Resistivity”). AASHTO T 288-12 is designed to test a soil sample’s electrical resistivity (ER) that correlates to its corrosion potential. However, the test, based on material passing through a No. 10 sieve, is inappropriate for coarse aggregate typically used by KDOT as the aggregate will be retained on a No. 10 sieve and potentially leads to over-conservative designs. However, ER imaging provides a two-dimensional (2D) profile of bulk ER of backfill material, thereby yielding more information regarding backfill uniformity compared to traditional sampling. The objective of this study was to characterize bulk ER of in-place MSE wall backfill aggregate. In this study, MSE walls selected by KDOT were tested using ER imaging during construction to determine bulk ER of the backfill. Variations within backfill ER may be a result of varying aggregate material, inclusions of fines, thoroughness of compaction, and the presence of water. ER imaging was used on five walls: four MSE walls and one gravity retaining wall that contained no reinforcement. One MSE wall contained metal reinforcement, while the other four walls contained geosynthetic. The ER imaging field method produced a 2D profile that depicted ER uniformity for bulk analysis. A post processing algorithm was generated to remove the subjective nature of the ER imaging results. The program determines the bulk ER based upon the ER imaging results. These results indicate that the laboratory analysis of AASHTO T 288-12 under-estimates the bulk ER of in-situ backfill material. Identification of a material’s bulk ER will help characterize the ER of aggregates in a complementary KDOT project. Results of this study will be used to recommend an in-situ test method for aggregate used by KDOT.
Keywords: Electrical Resistivity; Mechanically Stabilized Earth Retaining Walls; Coarse Aggregate Backfill; Civil Engineering (0543); Engineering (0537); Geological engineering (0466); Geophysical engineering (0467); Geophysics (0373)